Motivational Factors for Job Satisfaction among Librarians in University Libraries in Nigeria - J.N, Ekere (Journal of Home Economics Research, 2024)
The purpose of the study was to determine the motivational factors for job satisfaction among librarians in university libraries in Nigeria. Survey research design was employed to determine the factors that motivate librarians. A sample of 458 librarians from 31 university libraries in Nigeria was used. Questionnaire was the instrument used for data collection. The questionnaire was adapted from the Minnesota Satisfaction Questionnaire. Data were analyzed using mean. The finding showed motivational factors, including, among others, work itself, achievement, recognition, responsibility and advancement. Based on the findings it was recommended that university library management in Nigeria should promote the motivational factors among the librarians.